Developing expenditure questions: Findings from R1 cognitive testing - Jo d'Ardenne; Margaret Blake (Institute for Fiscal Studies (IFS), 2012)
Currently there is no established way to measure expenditure in the context of a general purpose survey. Therefore NatCen's Questionnaire Development Testing (QDT) Hub, working in collaboration with the Institute for Fiscal Studies and collaborators from Oxford and Cambridge Universities, are looking at how best to measure expenditure in a social survey context. This report provides findings from the cognitive testing of four different question formats: 1. A 'one-shot' question i.e. a single question asking 'How much did you spend on everything in the last month?' 2. A 'two-part' question i.e. two questions, one that asks about spending on essentials and one that asks about spending on everything else. 3. A 'breakdown' question i.e. that asks respondents to say how much they spend on each item on a list of common types of expenditure 4. And 'income minus surplus' question that asks respondents to work out how much money they receive per month and how much of that income remains unspent. It is possible that spending can be calculated from this information. This project is funded by the Nuffield Foundation.
Keywords: 330